Sticking it out : participation and discontinuation motives of young players in hockey : a New Zealand case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Sport Management at Massey University - Bowie, Cushla (Massey University, 2002)
The present study investigated the reasons why year 11, 12, 13 and recent school leavers in the Palmerston North/Manawatu area participated in, or discontinued playing hockey. A longitudinal case study was used as the research design involving three different time parts. Two hundred and eighty six subjects completed the participation or discontinuation motivation questionnaire, over the three stages, depending on whether they were participating in, or had discontinued from playing hockey. A mixed methodology approach was used to gather data, through questionnaires and interviews. A modified version of the Participation Motivation Questionnaire (PMQ) developed by Gill, Gross and Huddleston (1983) was used for the participation research, while discontinuation research was obtained based on the Sport Non-participation Scale (McNally & Orlick, 1977, cited in Ostrow, 1996) and Gaskin's Discontinuation Motivation Questionnaire (DMQ). The findings revealed multiple underlying motives for participation in hockey. A three-component factor solution in Stages One and Two demonstrated self, physical and team orientations, with Stage Three revealing a two factor solution, with self and physical/team orientations, as significant motives for participation in hockey. The findings indicate, that fun and enjoyment were salient factors in young peoples participation in hockey. Discontinuation results suggested a combination of motives as the most influential for participants' discontinuation in hockey including 'I wanted to do something else', 'I didn't have time to play hockey' and ' I wanted to play another sport'. The implications of these results for parents, coaches and administrators are that there needs to be a greater awareness as to individual's motives for playing or ceasing hockey participation. To maintain players, suggestion made are to make trainings stimulating and fun for players, help skill acquisition and improvement, provide time for players to be with friends in a learning environment. Parents, coaches and administrators need to work with practitioners to create programmes orientated toward satisfying motives of sport expressed by participants. Implications for practitioners are to be aware of changes facing youths as they enter the transitional phase, i.e. lifestyle changes, new friends, environment and teams. Areas for further research include carrying out more longitudinal studies looking at participants over a time period rather than just one moment in time. Also looking at the same sample over an extended time period to see how participant's orientation toward sport participation alters, this may also reveal whether participants who had discontinued had made a temporary or permanent decision. Qualitative in-depth interviews could be carried out with participants who have discontinued to provide the researcher with a more detailed understanding of why discontinuation took place.
Keywords: Hockey; Psychological aspects; Motivation (Psychology)